Modeling dependence structure of evidence from ASEAN-5 stock market patterns - Pattamon Pongkongkaew (2020)
© 2020, Universita Putra Malaysia. This paper was proposed to focus on the dependence structure of economics cycles (economic booms and recessions) among ASEAN-5 stock indexes which were the Philippines stock market (The Philippines Composite index: PSEi), Indonesia Stock market (Jakarta Composite Index: JCI), Malaysia stock market (FTSE Bursa Malaysia KLCI: FTSE), Thailand stock market (SET Index: SET) and Singapore Stock Market (The Straits Time Index: SGX). The data was transformed to be standardized residuals and observed as monthly samples during 2001 to 2018. Technically, Markov Switching Bayesian Vector Autoregressive model (MSBVAR) and CD-Vine Copula approaches were applied to do econometrical estimations in this study. The MSBVAR model was used to determine regime switching of the data set. For CD-Vine copula models, they were employed to computationally seek dependence structures. To exemplify each state of regimes, the Elliptical copula model was chosen to structurally define the relation among ASEAN-5 stocks. Empirically, the result represented the dynamics co-movement of each stock. CD-Vine copula trees showed that the PSEi index and JCI contained the strongly structural dependence in economic booming situations of the pre-crisis period. On the other hand, in the post-crisis period, PSEi had the strongly dependence connection with FTSE Bursa Malaysia. Thus, capital flows between Philippines and Indonesia were financially changed from flowing between Philippines and Indonesia to Philippines and Malaysia after crises. However, in the case of economic recessions, the result showed that there was the independent structure among ASEAN-5 stocks, both in pre-crisis and post crisis.